Regulatory Arbitrage in the Retail lending Market - D. A. Vysokov (Финансы: теория и практика, 2020)
The aim of the article is to analyze the features of regulatory arbitrage between credit and microfinance organizations in the retail lending market in Russia and to develop proposals to improve existing regulations on the activities of professional lenders. The work employed the methods of analysis, synthesis, generalization, as well as comparative legal research. The author found that regulatory arbitration might aim to get benefit from imperfect legislation. Signs of regulatory arbitration may indicate the inefficiency and redundancy of current legislation concerning the regulation of consumer lending. The author developed the following recommendations: to reduce redundant regulation regarding the limits of the full loan value for point-of-sale loans and installment loans; to switch to licensing system of financial organizations, considering the scale of their activities and the produced risks.